New records and new host-parasitoid interactions of phorids (Diptera: Phoridae) parasitizing leafcutter ants (Hymenoptera: Formicidae) in Argentina - Guillade, Andrea Cecilia (2017)
Leafcutter ants are one of the most important crop pests in the Neotropics. In the present study, several specimens were collected from four provinces in Argentina in order to determine the species of phorid flies parasitizing them. We report our findings on seven phorid species, Apocephalus neivai Borgmeier, Ap. noetingerorum Disney, Neodohrniphora unichaeta Disney, Myrmosicarius catharinensis Borgmeier, M. cristobalensis Disney, M. crudelis Borgmeier and M. gracilipes Borgmeier, over the leafcutter ants Acromyrmex ambiguus Emery, Ac. crassispinus Forel, Ac. heyeri Forel, Ac. lobicornis Emery andAc. lundii Guérin. All the known hosts and geographic ranges for these seven phorids in Argentina are provided. The seven phorid species represent new records for all the provinces studied, expanding their geographical ranges; furthermore, we establish a total of eleven new host-parasitoid interactions. Our data expand the knowledge of this little studied system and provide important considerations for the potential use of these parasitoids as biological control candidates of the leafcutter ants.